Evaluation of Midwives' Perceptions of Spirituality and Spiritual Care in Aydın, Turkey - Kızılca Çakaloz, Damla (Journal of religion and health, 2023)
Spirituality is an integral part of holistic care, but studies have revealed that the spiritual dimension of care is largely neglected in healthcare settings. This study evaluated midwives' perceptions of spirituality and spiritual care. The study is a cross-sectional design and was conducted from April 1 to June 30, 2018 in Aydın, Turkey. The research sample of the study contacted 101 midwives. The Spirituality and Spiritual Care Rating Scale were used to collect data. It was found that the midwives' perceptions of spirituality and spiritual care were affected by age, having children, family type, and working unit (p < 0.05).